Comparison of wide field imaging by nurses with indirect ophthalmoscopy by ophthalmologists for retinopathy of prematurity: a diagnostic accuracy study. Issue 8 (5th August 2020) - Athikarisamy, Sam Ebenezer; Lam, Geoffrey Christopher; Ross, Stuart; Rao, Shripada Cuddapah; Chiffings, Debbie; Simmer, Karen; Bulsara, Max K; Patole, Sanjay
Abstract : Objectives: Retinopathy of prematurity (ROP) is a vasoproliferative disease of the preterm retina with the potential to cause irreversible blindness. Timely screening and treatment of ROP are critical. Neonatal nurses trained in wide field digital retinal photography (WFDRP) for screening may provide a safe and effective strategy to reduce the burden of ophthalmologists in performing binocular indirect ophthalmoscopy (BIO). The objective of the study was to determine the diagnostic accuracy of WFDRP in the diagnosis of referral warranting ROP (RWROP). Design: Prospective diagnostic accuracy study. Setting: A tertiary neonatal intensive care unit in Perth, Western Australia. Participants: Preterm infants who fulfilled the Australian ROP screening criteria (gestational age (GA) <31 weeks, birth weight (BW) <1250 g). Intervention: Sets of 5–6 images per eye (index test) were obtained within 24–48 hours prior to or after the BIO (reference standard), and uploaded onto a secured server. A wide field digital camera (RetCam, Natus, Pleasanton, California, USA) was used for imaging. A paediatric ophthalmologist performed the BIO. The ophthalmologists performing BIO versus reporting the images were masked to each other's findings. Primary outcome: The area under the receiver operating characteristic (ROC) curve was used as a measure of accuracy of WFDRP to diagnose RWROP. Results: A total of 85 infants (mean BW; 973.43 g, mean GA; 29 weeks) underwent a median of two sessions of WFDRP. There were 188 episodes of screening with an average of five images per eye. WFDRP identified RWROP in 7.4% (14/188 sessions) of examinations. In one infant, BIO showed bilateral plus disease and WFDRP did not pick up the plus disease. WFDRP image interpretation had a sensitivity of 80%, specificity of 94.5% for the detection of RWROP. The 'area under the ROC curve' was 88% when adjusted for covariates. Conclusions: WFDRP by neonatal nurses was feasible and effective for diagnosing RWROP in our set up. Trial registration number: ACTRN12616001386426.